ETUDE DU RÉGIME HYDROLOGIQUE DU FLEUVE INAOUÈNE, MAROC SEPTENTRIONAL - Jamal, Naoura; Benaabidate, Lahcen (European Scientific Journal, ESJ, 2014)
The analysis of the Inaouene river hydrologic behavior has shown a mediterranean typical regime, characterized by the abundance of rain with high winter flow rates, therefore, heavy flooding, and on the other hand, by a strong dry season, thus, low flow. The annual module, as well as the different coefficients, highlights the hydroclimatic fluctuations, in relationship with a semi-arid climate. The hydrological balance highlighted the importance of water volumes routed upstream and downstream, confirming the morphometric parameters of the basin and the lithologic nature which involves two major different units (formations essentially karstic carbonate in the Middle Atlas at the Southern part of the basin and, a marly impermeable substratum in the Prerif; northern part of the basin). The frequency study of extreme high flow rates showed that they are not governed by a specific law.